Endourology Methods in Pediatric Population for Kidney Stones Located in Lower Calyx: FlexURS vs. Micro PCNL (MicroPERC®) - Halinski, Adam; Steyaert, Henri; Wojciech, Magdalena; Sobolewski, Bartłomiej; Haliński, Andrzej (Frontiers in Pediatrics, 2021)
Kidney stone disease in children is always a therapeutic challenge. It is a multifactorial condition and it should be approached, diagnosed and treated as such. One of the biggest challenges is stone in the lower calyx. There are three main techniques to treat this condition: ESWL – Extracorporeal Shock Wave Lithotripsy, RIRS - Retrograde IntraRenal Surgery, and PCNL - PerCutaneous Nephro-Lithotrypsy. In paediatric population, the most frequently used is ESWL, and in the event of failure, endoscopic procedures are the second-best choice. In this article, a sample of 53 children admitted to a tertiary medical center was examined. 38 of those underwent RIRS, while the remaining 15 - microPCNL. The average size of the deposit was 1.22 mm and 1.35 retrospectively. The Stone Free Rate (SFR) was achieved in RIRS at 84.21% and at 86.7% in microPERC. RIRS and MicroPERC are two comparably effective methods for treating lower calyx stones. According to our data, RIRS carries a lower risk of complications and hospital stay (mean of 3 days). The learning curve for these procedures in paediatric urology is long and relies on a limited number of patients. The number of patient for these procedures is restricted, due to the high efficacy of ESWL. Radiation exposure is an important factor, due to ALARA protocol. ESWL remains the treatment of choice for KSD in children and can be performed under ultrasound control. For many parents, it is a first-choice treatment preference for their child due to its safety and efficacy.